Dexmedetomidine induced hypotension and hemostatic markers - Gehan M Eid; Shaimaa F Mostafa; Mohamed M Abu Elyazed (Wolters Kluwer Medknow Publications, 2023)
Background and Aims: The hemostatic system undergoes extensive alterations following surgical trauma leading to a hypercoagulable state. We assessed and compared the changes in platelet aggregation, coagulation, and fibrinolysis status during normotensive and dexmedetomidine-induced hypotensive anesthesia in patients undergoing spine surgery. Material and Methods: Sixty patients undergoing spine surgery were randomly allocated into two groups: normotensive and dexmedetomidine-induced hypotensive groups. Platelet aggregation was assessed preoperatively, 15 min after induction, 60 min, and 120 min after skin incision, at the end of surgery, 2 h and 24 h postoperatively. Prothrombin time (PT), activated partial thromboplastin time (aPTT), platelet count, antithrombin III, fibrinogen, and D-dimer levels were measured preoperatively, 2 h and 24 h postoperatively. Results: Preoperative platelet aggregation (%) was comparable between both groups. Platelet aggregation significantly increased intraoperative at 120 min after skin incision and postoperatively in the normotensive group compared to the preoperative value (P < 0.05) but it was insignificantly decreased during the intraoperative induced hypotensive period in the dexmedetomidine-induced hypotensive group (P > 0.05). Postoperative PT, aPTT significantly increased and platelet count, and antithrombin III significantly decreased in the normotensive group compared to the preoperative value (P < 0.05) but they were not significantly changed in the hypotensive group (P > 0.05). Postoperative D-dimer significantly increased in the two groups compared to the preoperative value (P < 0.05). Conclusion: Intraoperative and postoperative platelet aggregation significantly increased in the normotensive group with significant alterations of the coagulation markers. Dexmedetomidine-induced hypotensive anesthesia prevented the increased platelet aggregation that occurred in the normotensive group with better preservation of platelet and coagulation factors.